Verbal and Symbolic Aggression Female in The Madurese Culture - Haliq, Fathol; Hidayati, Tatik; Ariwidodo, Eko; Hanurawan, Fattah; Atmoko, Adi (Universitas Islam Negeri Madura, 2023)
This research explores the verbal and symbolic aggression of Madurese women students. These two things will be examined as the leading models by looking at the oral and symbolic aggression models for Madurese women. Women’s aggression is a complex form of behavior. This complexity is essential to the cyclical activities of the self and its environment. Madurese women ‘do not have a voice’ in voicing their own opinions including in rural electoral power politics and household economic autonomy. This research uses mixed methods, quantitative and qualitative. Quantitative research uses statistical analysis using confirmatory factorial analysis (CFA), while qualitative research uses descriptive data about the types and forms of verbal aggression in women. Both explore verbal and symbolic tendencies of aggression in Madurese women. The women involved were students at universities in Madura. The research results show that women prefer symbolic aggression to verbal aggression. Women with higher education prefer symbolic aggression to verbal aggression. Types and forms of verbal aggression include cha’-nguca’e, hitting, pulling, harming, and injuring. This oral does not lead to the loss of another person's life. Another finding is that a symbolic attack always follows every verbal aggression. Meanwhile, symbolic aggression involves gossip, talking about bad things about other women with slander and backbiting, spitting on other people’s property rights, inviting other people to hate other women, constantly talking about other people’s bad things, looking for reasons to hate other people, not coming meeting with hated people.